1989
DOI: 10.1016/s0006-3495(89)82871-1
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength regulation in iodopsin, a cone pigment

Abstract: The opsin shift, the difference in wavenumber between the absorption peak of a visual pigment and the protonated Schiff base of the chromophore, represents the influence of the opsin binding site on the chromophore. The opsin shift for the chicken cone pigment iodopsin is much larger than that for rhodopsin. To understand the origin of this opsin shift and the mechanism of wavelength regulation in iodopsin, a series of synthetic 9-cis and 11-cis dehydro- and dihydro-retinals was used to regenerate iodopsin-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 21 publications
5
26
1
Order By: Relevance
“…Figure 2 shows the absorption spectrum from the protonated Schiff base of 6-s-cis,9-cis-retinal, whose wavelength of maximal sensitivity (Amax) was 467 nm. Absorption spectra of the protonated Schiff-base forms of 11-cis-and 9-cis-retinal were also measured; their maxima were 440 and 439 nm, respectively, in good agreement with published data (see Chen et al 1989 Chromophores were delivered to bleached cones in lipid vesicles (Perlman, Nodes & Pepperberg, 1982;Corson, Cornwall, Crouch & Mani, 1988;Jones, Crouch, Wiggert, Cornwall & Chader, 1990). Vesicles were prepared by drying 50 Al of L-a-phosphatidylcholine (Sigma) under nitrogen, then adding 500fl1 of Ringer or Locke's solution and sonicating on ice until clear, about 10-15 min.…”
Section: Preparation Of Chromophores and Lipid Vehiclessupporting
confidence: 83%
See 2 more Smart Citations
“…Figure 2 shows the absorption spectrum from the protonated Schiff base of 6-s-cis,9-cis-retinal, whose wavelength of maximal sensitivity (Amax) was 467 nm. Absorption spectra of the protonated Schiff-base forms of 11-cis-and 9-cis-retinal were also measured; their maxima were 440 and 439 nm, respectively, in good agreement with published data (see Chen et al 1989 Chromophores were delivered to bleached cones in lipid vesicles (Perlman, Nodes & Pepperberg, 1982;Corson, Cornwall, Crouch & Mani, 1988;Jones, Crouch, Wiggert, Cornwall & Chader, 1990). Vesicles were prepared by drying 50 Al of L-a-phosphatidylcholine (Sigma) under nitrogen, then adding 500fl1 of Ringer or Locke's solution and sonicating on ice until clear, about 10-15 min.…”
Section: Preparation Of Chromophores and Lipid Vehiclessupporting
confidence: 83%
“…Chromophore replacement has also confirmed that part of the opsin shift in bacteriorhodopsin is produced by the protein's twisting the chromophore into the planar 6-s-trans conformation (Harbison, Smith, Pardoen, Courtin, Lugtenburg, Herzfeld, Mathies, Griffin, 1985;Lugtenburg, Muradin-Szweykowska, Heeremans, Pardoen, Harbison, Herzfeld, Smith & Mathies, 1986;van der Steen, Biesheuvel, Mathies & Lugtenburg, 1986). A similar mechanism has been proposed to account for part of the red shift in the chicken cone pigment iodopsin (Chen, Nakamura, Ebrey, Ok, Konno, Derguini, Nakanishi & Honig, 1989).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Such a model, with chloride ion binding near where the polyene chain connects to the ring, is also consistent with synthetic chromophore studies of this pigment which position a negative charge near C7. 76 The simplest interpretation of the P521 data is therefore that a chloride ion bound near the ring has its binding constant affected by a relaxation which creates BSI. Since the chloride binding site is known to be composed of two positive charges, His-l96 and Lys-199 (corresponding to positions 181 and 184 in bovine rhodopsin),":" it is that area of the protein which would be affected directly by a change in the chromophore when BSI is formed.…”
Section: Batho To Lumi Processes In Other Visual Pigmentsmentioning
confidence: 99%
“…Like rhodopsin, iodopsin contains li-cis-retinal as its chromophore. Investigations with retinal isomers and analogs suggested that iodopsin and rhodopsin have similarly shaped chromophore binding sites (6) but the point charges are in different locations (6,7).…”
mentioning
confidence: 99%